Riesgos psicosociales en la calidad de vida laboral de los funcionarios de la Cooperativa de Transporte Reina del Camino, cantón Chone - Romero Zambrano, Lisbeth Antonella (2022)
The objective of this research was to evaluate the incidence of psychosocial risks on the quality of working life of the employees of the “Reina del Camino” Transport Cooperative, Chone town. The psychosocial risks in the workers were determined by collecting and analyzing information from the Cooperative with visits to the study site and application of interviews, obtaining a total of 135 people working in the institution divided into two areas: administrative and operational. Likewise, a review of compliance with current Occupational Health and Safety regulations was carried out, where it was observed that the cooperative complies with all the items identified; Finally, psychosocial risks were evaluated using a questionnaire from the Ministry of Labor of Ecuador, concluding that the personnel are exposed to a medium level of psychosocial risk with a frequency of 98%. Subsequently, the quality of working life was estimated by applying a questionnaire based on the Walton model, which assesses eight fundamental dimensions and the correlation between them; It was concluded that the quality of work life of the study site according to the perception of the workers is high with a score of 109.27 and has a strong positive correlation with 6 of the 8 dimensions identified. With the results obtained, an identification matrix and a psychosocial risk prevention program were established for the “Reina del Camino” Transport Cooperative, which was socialized with the cooperative's staff.